Eimeria infections of plateau pika altered the patterns of temporal alterations in gut bacterial communities - Li, Maoping; Wang, Suqin; Zhong, Liang; Heděnec, Petr; Tan, Zhaoxian; Wang, Rong; Chen, Xinyang; Zhang, Yan; Tang, Bingmin; Zhou, Huakun; Qu, Jiapeng (Frontiers in Microbiology, 2024)
Intestinal parasites, such as Eimeria, are common among plateau pika (Ochotona curzoniae). The gut microbiome is an essential driver of the host response to gastrointestinal parasites. However, the effects of intestinal protozoal parasites on the temporal variations in the gut microbiome and behavioral and physiological activities remain unknown. Our study conducted treatments involving experimental feeding of pika with Eimeria oocysts or anticoccidia under laboratory conditions to focus on the parasite-associated alterations in gut bacterial communities, host behavioral activity, physiology, and host–bacteria relationships. The results showed insignificant differences in bacterial community structures among treatments on the basis of Bray–Curtis distance metrics, whereas the patterns of temporal alterations in the bacterial communities were changed by the treatments. Bacterial alpha diversities did not vary with the treatments, and experimental feeding with Eimeria slowed down the decrement rate of alpha diversity. Furthermore, few bacterial members were significantly changed by the treatments—only the genus Ruminococcus and the species Ruminococcus flavefaciens, which were associated with energy metabolism. Experimental feeding with Eimeria modified the temporal variations in the bacterial members, including a lower loss rate of the relative abundance of the dominant families Muribaculaceae and Ruminococcaceae in the group with Eimeria experimental feeding. Moreover, a shifting energy trade-off was suggested by the parasite-induced increments in thyroid hormones (triiodothyronine and tetraiodothyronine) and decrements in exploration behavior in the group with Eimeria feeding. However, we did not detect specific connections between gut bacterial communities and pika behaviors and physiology in terms of energy trade-offs. Further in-depth research is needed to examine the role of Eimeria-modified differences in the gut bacteria of plateau pika.